A probabilistic approach for optimizing inspection, monitoring, and maintenance actions against fatigue of critical ship details. (May 2016) - Soliman, Mohamed; Frangopol, Dan M.; Mondoro, Alysson
Highlights: Comprehensive approach for planning inspection, monitoring, and repair under fatigue. Interventions minimize life-cycle cost and maintenance delay, and maximize service life. Optimum inspection, monitoring, and repair times and monitoring duration are achieved. Life-cycle cost includes inspection, monitoring, repair, and expected failure cost. Uncertainties in damage propagation, inspection and monitoring outcomes are considered. Abstract: Fatigue is one of the main deteriorating mechanisms that affect the safety and reliability of ship structures. Fatigue cracks can appear at various locations along the ship structure and may occur at early stages in the service life of a ship. Inspection, monitoring and/or repair actions are applied to prevent sudden failures of damaged structural components and their associated consequences. However, these actions increase the operational cost of the ship and should be optimally planned during its service life. Due to the presence of significant uncertainties associated with crack initiation and propagation, the planning of such actions should be performed probabilistically. In this paper, a probabilistic approach for inspection, monitoring, and maintenance optimization for ship details under fatigue effects is proposed. Based on the stress profile and the crack geometry at the damaged location, intervention times and types are determined by solving an optimization problem which simultaneously minimizes the life-cycle cost, maximizes the expected service life, and minimizes the expected maintenance delay over the life-cycle. The life-cycle cost includes the cost of inspection, monitoring, and maintenance actions, as well as the cost of failure of the detail. The proposed approach is applied to a side shell detail of a steel ship.